THE EFFECTIVENESS OF RECIPROCAL TEACHING IN TEACHING READING COMPREHENSION OF DESCRIPTIVE TEXT - Oktavianti, Desy; Sada, Clarry; Suhartono, Luwandi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe aim of this research was to investigate the effectiveness of reciprocal teaching in reading comprehension of descriptive text in the eight- Grade students of SMP N 02 Sejangkung in Academic Year 2017/ 2018. The population of this research was all of eight- grade students of SMP N 02 Sejangkung in Academic Year 2017/ 2018 and the sample was taken from Class C which consists of 31 students. The writer conducted this research through pre- experimental research with one group pre- test and post- test design. The writer collected the data by using a measurement technique to measure students reading comprehension of descriptive text. The findings showed that the t-test was higher than t-table and the effect size was categorized as a strong effect. In conclusion, the use of reciprocal teaching is significantly effective in teaching reading comprehension of descriptive text. Therefore, the alternative hypothesis which stated â€œThe effectiveness of reciprocal teaching in reading comprehension of descriptive text in eight- grade students of SMP N 02 Sejangkung in Academic Year 2017/2018â€ was accepted.Keywords: Reciprocal Teaching, Reading Comprehension, Descriptive Text, Pre- Â Â Â Â Â Â Â Experimental Study